Mass Cultivation of Entomopathogenic Nematode in Artificial Media - Dyah Rini Indriyanti; Nur Lailatul Muharromah (Biosaintifika: Journal of Biology & Biology Education, 2016)
Entomopathogenic nematodes Entomopathogenic nematodes (EPN) of the genera Heterorhabditis and Steinernema are commercially used to control pest insect. EPN is widely cultivated through in-vivo and in vitro methods. This research aims to discover the abundance of EPN cultivated in various artificial media. Seven types of media composition were tested in this research: media A (yeast + soybean powder), media B (yeast + chicken liver), media C (yeast + dog food), media D (yolk + soybean powder), media E (yolk + chicken liver), media F (yolk + dog food), and media G (yeast + yolk + dog food). Each media was inoculated in 1.2x103JI/mL. The growth of EPN was observed weekly in 4 weeks. Results showed that EPN could be cultivated using various media; media D, E, F, and G. Highest abundance of EPN is found in the second week of media D for 28164 JI/ml.Cell harvesting is suggested to be conducted during the first and second week to obtain maximum abundance of EPN.How to CiteIndriyanti, D., Muharromah, N. (2016). Mass Cultivation of Entomopathogenic Nematode In Artificial Media. Biosaintifika: Journal of Biology Biology Education, 8(1), 111-118.